2023
DOI: 10.3390/fermentation9050482
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Bacillus pumilus LYMC-3 to Antagonize Sphaeropsis sapinea

Abstract: Bacillus pumilus is widely used as a biocontrol agent. To further develop the biological control potential of B. pumilus LYMC-3 against pine blight, a statistical experimental design was used to optimize a liquid medium using low-cost substrates to improve its antagonistic activity against Sphaeropsis sapinea. Through the plate antagonism test and greenhouse control effect test, this study determines the antifungal effect of strain LYMC-3 against S. sapinea and pine blight. Moreover, response surface optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…This could be attributed to the fact that monosaccharides are easier for the organism to absorb and utilize, leading to the production of inhibitory substances compared to disaccharides and polysaccharides. Our finding is in line with those obtained by Pan et al (2023) who optimized glucose as a carbon source for Bacillus pumilus LYMC-3 fermentation to improve the synthesis of inhibitory substances. Similarly, in Streptomyces tanashiensis strain A2D, Streptomyces padanus PMS-702, and Streptomyces griseocarneus , glucose proved to be the most optimal carbon source for the synthesis of antifungal polyenes ( Zheng et al, 2000 ; Wu et al, 2008 ; Singh et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be attributed to the fact that monosaccharides are easier for the organism to absorb and utilize, leading to the production of inhibitory substances compared to disaccharides and polysaccharides. Our finding is in line with those obtained by Pan et al (2023) who optimized glucose as a carbon source for Bacillus pumilus LYMC-3 fermentation to improve the synthesis of inhibitory substances. Similarly, in Streptomyces tanashiensis strain A2D, Streptomyces padanus PMS-702, and Streptomyces griseocarneus , glucose proved to be the most optimal carbon source for the synthesis of antifungal polyenes ( Zheng et al, 2000 ; Wu et al, 2008 ; Singh et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, microorganisms need the right carbon-to-nitrogen ratio for their growth and metabolism ( Ray et al, 2007 ). A low carbon-to-nitrogen ratio can result in excessive growth, premature senescence, and autolysis of the bacteria, whereas low fermentation density is caused by a high carbon-to-nitrogen ratio that is unfavorable to the bacteria’s ability to reproduce ( Pan et al, 2023 ). In the present study, the nitrogen source (beef extract) exhibited the highest nematicidal potential of 84%, indicating that it is a suitable nitrogen source for nematode control.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer the activated NJSZ-13 into an NB medium triangular flask and place it on a shaking table at 200 R/min and 28 • C for 4 days; the obtained shaking culture solution was the fermentation broth. The supernatant obtained by centrifugation was the fermentation filtrate [21].…”
Section: Obtaining Of the Bacterial Suspension And Fermentation Filtratementioning
confidence: 99%
“…Laboratory-based fermentation process optimization typically utilizes one-way tests combined with orthogonal tests to swiftly identify the optimal fermentation medium ratio. Through fermentation optimization, Pan [11] increased the antifungal rate of B. pumilus LYMC-3 against the pathogen of pine shoot blight by 15.84% compared to before optimization. Dai [12] optimized the fermentation conditions of Bacillus pumilus HR10 to achieve an 87.04% inhibition of Sphaeropsis sapinea.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experiments have revealed that the B. pumilus LYMC-3, a strain with a potent antagonistic effect, was isolated from Pinus massoniana stems. It exhibited a broad spectrum of antifungal inhibition and a strong inhibitory effect on the poplar canker pathogen (P. macrospora) and the pine shoot blight pathogen (S. sapinea) [11,16]. It also has strong nematicidal activity against Bursaphelenchus xylophilu, which is the causal agent of pine wilt disease.…”
Section: Introductionmentioning
confidence: 99%